Influence of rain tree (Samanea saman) pods with concentrate on nutrients intake and digestibility in HF x Deoni heifers - JAGGINAVAR, K B; HOSAMANI, S V; NAIK, D G (The Indian Journal of Animal Sciences, 2014)
In this investigation 24 HF x Deoni crossbred heifers of 12 months age and 160 kg body weight were randomly distributed into 4 groups of 6 each to study the influence of rain tree (Samanea saman) pods with concentrate on nutrients intake and digestibility in HF Deoni heifers. All the heifers were offered ad lib. green paragrass. Bengalgram and jowar straw. Concentrate and rain tree pods were offered to meet the requirement as treatment 1: 100% concentrate + 0% pods, treatment 2:75% concentrate + 25% pods, treatment 3:50% concentrate + 50% pods and treatment 4:0% concentrate + 100% pods. Rain tree pods contain high protein (15,63%), nitrogen free extract (58.34%) and low fibre (19.77%) and silica (0.17%). Tbe intake of green and dry roughages did not differ statistically between treatments. Intakes of DM, DCP and TDN were signiticantly (P<0.05) higher in treatments 1 and 2 over treatment 4. The digested OM, CP, were significantiy (P<0.05) higher in treatments 1 and 2 over treatment 4. The digestibility of CP was significantly (P<0.05) higher in treatments 1, 2 and 3 over treatment 4, whereas, the digestibility of other nutrients was statistically similar in all the treatments. Hence it is inferred from the study that the mill tree pods can be incorporated up to 50% level by replacin isocaioric and isonitrogcnous concentrate mixture without affecting the intake and digestibility of nutrients in HF x Deoni crossbred heifers.